Reading components and oral reading fluency among english second language learners - Ling, Hie Ping (Universiti Malaysia Sarawak, (UNIMAS), 2019)
Oral reading fluency is one of the six components of reading competency along with word reading accuracy (WRA), word reading efficiency (WRE), phonological awareness (PA), rapidly automatized naming (RAN), and phonological memory (PM). It is related to reading comprehension and it can be used to predict a reader's reading competency. However, this study was limited to English as a second language among primary school students. The purpose of this study was to examine the relationship between reading components and oral reading fluency and to determine if oral reading fluency predicts reading comprehension. The participant of this comprised 866 years Primary 1 students from different schools in Kuching. Difference kinds of measurements were used in this research to find out if reading comprehension has a correlation with oral reading fluency. Besides that, the fmal data obtained were analyzed using a correlation and multiple regression analysis. Pearson correlation test was used to determine the correlation between reading components and oral reading fluency and the relationship between oral reading fluency reading comprehension; the multiple linear regression was tested to determine if the reading components predict oral reading fluency and reading comprehension.